Somatic construction and performance of 13-year general kayakers in Kujawsko - Pomorskie and Wielkopolska Province - Tracz, Marta Barbara; Napierała, Marek; Gotowski, Rafał (Journal of Education, Health and Sport, 2016)
The aim of the study was to demonstrate to the provinces where young people kayaking is characterized by a higher level of overall efficiency they represent the type of physique. The study was conducted among 38 kayakers, canoeists 15 from the Kujawsko-Pomorskie and 20 kayakers and canoeists 19 of the Wielkopolska region at the age of 13 years. To measure the motor skills used in an attempt International Physical Fitness Test, and to build somatic body weight and height, determined slim body shape. Conclusions: (1) The kayakers from both regions studied are similar in height and weight, while Canoeists from the Wielkopolska region characterized by greater height and weight than their peers from the Kujawsko-Pomorskie, (2) Young athletes who joined the studies represent the most common type of construction leptosomatic, (3) The efficiency of the overall kayakers and canoeists ranks at a medium level, (4) The efficiency of the overall canoeists and kayakers from the Wielkopolska region is higher than their peers from the Kujawsko-Pomorskie.